The use of complementary approaches for conservation biological control: carabid and staphylinid beetles as natural enemies of the olive fruit fly - Albertini, Alice (2020)
Trabalho apresentado em 8th IOBC-WPRS meeting on Integrated Protection of Olive Crops, 4-7 Junho 2018, Florença, Itália